Grammatical Ellipsis in Abu Ali al-Farisi’s Book "al-Ighfal" (d. 377 AH): A Study and Analysis - Amin Ali, Azad Hama (Journal of Tikrit University for Humanities, 2025)
Ellipsis is an important linguistic phenomenon used by all languages, and the human soul tends to abbreviate everything, including the speech people use, and deletion includes the morphological and syntactic levels, and we limited ourselves in this study to grammatical deletion in Abu Ali Al-Farsi’s book Al-Ighfal. The present study deals with the grammatical deletion in the book Al-Ighfal by Abu Ali Al-Farsi (d. 377). The importance of studying this phenomenon lies in the fact that it helps us understand grammatical structures, especially the meanings resulting from deletion in the Qur’anic verses that Al-Farsi dealt with in his book.